Examining healthcare needs and decisions to seek health services among Venezuelan migrants living in Trinidad and Tobago using Andersen's Behavioral Model - Nyla Lyons; Brendon Bhagwandeen (Frontiers Media S.A., 2023)
IntroductionBeginning in 2016, Trinidad and Tobago experienced increasing flows of migrants and refugees from Venezuela. Through a Government Registration Exercise in 2019, followed by a Re-registration Exercise in 2020, migrants and refugees benefitted from access to publicly available primary care and emergency medical services. By applying Andersen's Behavioral Model for Health Service Use, our study examined the non-communicable disease care needs of migrants, and factors influencing their decision to seek public and private health services.MethodBetween September and December 2020, a health questionnaire was administered via telephone to n = 250 migrants from Venezuela. Descriptive statistics summarized the constructs of Andersen's Behavioral Model. The model comprised of predisposing factors including migrants' social characteristics; enabling factors namely monthly earnings, education level and most trusted source of information on medical needs; need for care factors such as migrants self-reported health status, presence of non-communicable health conditions and having visited a doctor in the past 12 months; and the outcome variables which were migrants' decisions to seek public and private health services. Pearson χ2 tests, odds ratios and multivariable logistic regression with backward elimination examined the factors influencing a migrant's decision to seek health services.ResultsOverall, 66.8% of migrants reported they would seek public health services, while 22.4% indicated they would seek private health services. Predisposing factors namely length of time residing in Trinidad and Tobago (p = 0.031) and living with family/friends (p = 0.049); the enabling factor of receiving information from publicly available sources (p = 0.037); and the need for care factor of visiting a doctor for a physical health problem (p = 0.010) were significant correlates of their decision to seek care in the public sector. Predisposing factors namely living with family/friends (p = 0.020) and the enabling factor of having difficulty accessing healthcare services (p = 0.045) were significant correlates of their decision to seek care from private providers.DiscussionOur findings demonstrated the positive association between social networks and a migrant's decision to use public and private health services, thus underscoring the importance of family and friends in facilitating health service use, promoting proper health practices and preventing diseases. Overall, the use of Andersen's Behavioral Model aided in identifying the factors associated with the use of health services by Venezuelan migrants in Trinidad and Tobago. However, further studies are needed to better understand their need for ongoing care, to inform policy, and to plan targeted health interventions for addressing the gaps in health service access, barriers and use.